Biochemical and Hematological Markers of Iron Status of the Populations in the Lekie Division of Cameroon - Guy Noah; Elie Fokou; Fadimatou Bebbe; Eposi Haddison; Gilbert Ghislain Mbassi Manga; Raoul Kemzeu; Géneviève Nomo Nga; Vicky Ama Moor (International Journal of Nutrition, 2025)
Iron deficiency is a major public health problem worldwide. It affects a significant proportion of the population, and is responsible for around 50% of anemia cases worldwide. Cameroon in general and Lekie Division in particular, is very highlyaffected by this problem. However, early detection of the problem can prevent the fatalities associated to it. The objective of this study was to provide up-to-date, detailed data on the markers of iron status in these populations, so that treatment can be better targeted. A two-month cross-sectional study was conducted in the Lekie Division in collaboration with local health centres in both urban and rural areas. The study sample consisted of 361 participants of all age groups and sexes. A questionnaire was issued to obtain information of the participants socio-demographic status, then 3 to 5ml of blood were collected and a number of markers of the participants iron status were studied. Of all the hematological markers studied, hemoglobin concentration in the study population was below normal in both men and women. Biochemical markers were good for all socio-demographic parameters. The mean values of biochemical and hematological markers in the population of the Lekie Division were good for all socio-demographic parameters, with the exception of hemoglobin concentration, which remains critical, requiring particular attention in this locality, but above all urgent intervention lest the situation aggravates further.
Keywords: Biochemical and Hematological Markers